2016
DOI: 10.1002/2015wr017663
|View full text |Cite
|
Sign up to set email alerts
|

Imprecise probabilistic estimation of design floods with epistemic uncertainties

Abstract: An imprecise probabilistic framework for design flood estimation is proposed on the basis of the Dempster-Shafer theory to handle different epistemic uncertainties from data, probability distribution functions, and probability distribution parameters. These uncertainties are incorporated in cost-benefit analysis to generate the lower and upper bounds of the total cost for flood control, thus presenting improved information for decision making on design floods. Within the total cost bounds, a new robustness cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Qi et al (2016) employed a subsampling ANOVA approach (Bosshard et al, 2013) to quantify individual and interactive impacts of the uncertainties in data, probability distribution functions, and probability distribution parameters on the total cost for flood control in terms of flood peak flows. Even though the subsampling ANOVA approach is able to reduce the effect of the biased estimator on quantification of variance contribution resulting from the traditional ANOVA approach, it should be noticed that merely subsampling one uncertainty parameter/factor (referred to as single-subsampling ANOVA), as used in the studies by Bosshard et al (2013) and Qi et al (2016a), will lead to (i) an underestimation of the individual contribution for the factor to be sampled and (ii) overestimation of contributions from those non-sampled factors. Moreover, few studies have been reported to characterize the individual and interactive effects of parameter uncertainties in marginal and dependence models on the multivariate risk inferences.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al (2016) employed a subsampling ANOVA approach (Bosshard et al, 2013) to quantify individual and interactive impacts of the uncertainties in data, probability distribution functions, and probability distribution parameters on the total cost for flood control in terms of flood peak flows. Even though the subsampling ANOVA approach is able to reduce the effect of the biased estimator on quantification of variance contribution resulting from the traditional ANOVA approach, it should be noticed that merely subsampling one uncertainty parameter/factor (referred to as single-subsampling ANOVA), as used in the studies by Bosshard et al (2013) and Qi et al (2016a), will lead to (i) an underestimation of the individual contribution for the factor to be sampled and (ii) overestimation of contributions from those non-sampled factors. Moreover, few studies have been reported to characterize the individual and interactive effects of parameter uncertainties in marginal and dependence models on the multivariate risk inferences.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al (2016) employed a subsampling ANOVA approach (Bosshard et al, 2013), to quantify individual and interactive impacts of the uncertainties in data, probability distribution functions, and probability distribution parameters on the total cost for flood control in terms of flood peak flows. Even though the subsampling ANOVA approach is able to reduce the effect of the biased estimator on quantification of variance contribution resulting from traditional ANOVA approach, it would be noticed that merely subsampling one uncertainty parameter/factor (referred as single-subsampling ANOVA), as used in the studies by Bosshard et al (2013) and Qi et al (2016a), will lead to underestimation of individual contribution for the factor to be sampled and overestimation of contributions for those non-sampled factors. Moreover, few studies have been reported to characterize the individual and interactive effects of parameter https://doi.org/10.5194/hess-2019-434 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty analysis allows the identification of uncertain parameters (Tung & Yen, 2005), a quantitative assessment of model reliability (Merz & Thieken, 2005;Montanari & Koutsoyiannis, 2012;Tung & Yen, 2005), and it provides a means of analyzing the robustness of flood risk management decisions. Furthermore, an analysis of the contribution of individual sources indicates where potential improvements in the method could have the greatest impact (Cullen & Frey, 1999;Hall & Solomatine, 2008;Sikorska et al, 2012) and therefore how uncertainty could be reduced (Qi et al, 2016), which is especially important for ungauged catchments (Sikorska et al, 2012). Although, uncertainty cannot be eliminated, its assessment at least enables its management (Koutsoyiannis, 2014).…”
Section: Introductionmentioning
confidence: 99%